x^2 - 14x + .... = 17 + ....
x^2 - 14x + 49 = 17+ 49
(x-7)^2 = 66
x-7 = ± √66
x = 7 ± √66
by formula:
x = (14 ± √(14^2 - 4(1)(-17))/2
= (14 ± √264)/2
= (14 ± 2√66)/2
= 7 ± √66
When the coefficient of x^2 is 1 and the middle term is even, I always use "completing the square" rather than the formula. Notice you get the answer already in simplified form
(a) Complete the square by writing in the form . Note: the numbers and can be positive or negative.
x^2-14x-17=(x-7)^2+
(b) Solve the equation by completing the square or using the quadratic formula. If there is more than one correct answer, enter your answers as a comma separated list. If there are no solutions, enter NONE.
x^2-14x-17=0
I keep getting this wrong but I don't know why.help please
1 answer